The impact of a non-functioning pituitary adenoma on life – A qualitative study of patients’ experiences - Nasrin Al-Shamkhi; Britt Edén Engström; Eva Rask; Agneta Anderzén-Carlsson (PLoS ONE, 2026)
Purpose Most studies regarding quality of life in patients with non-functioning pituitary adenoma are based on general questionnaires that might not capture disease-specific aspects, making further exploration of patients’ experiences with non-functioning pituitary adenoma necessary. This study aimed to describe how patients that have undergone surgery due to non-functioning pituitary adenoma experience the effects of the disease on their life. Methods Semi-structured interviews were held with eight participants who had undergone surgery due to non-functioning pituitary adenoma. Participants were recruited from an outpatient endocrinology clinic at a tertiary hospital in Sweden. Inductive qualitative content analysis was used. Results The analysis identified an overarching theme, Life has changed but not necessarily for the worse , and three subthemes: The knowledge about the tumour evoked existential concerns , Suffering became a part of life and Finding comfort in a new everyday life. Conclusion The findings show that the participants’ lives have changed due to non-functioning pituitary adenoma. While this change was not always for the worse, the quality of life was negatively impacted for some, despite optimal treatment. A changed view on life and general trust in the healthcare system could temper the impact of non-functioning pituitary adenoma. Moreover, communication between healthcare professionals and patients remains a central aspect of patients’ experiences.